2019
DOI: 10.4236/jbpc.2019.102002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change in Dimyristoyl Phosphatidyl Choline (DMPC) Molecule Alkyl Chains on the Addition of Cholesterol to DMPC Monolayer: Specific Addition Effect of Cholesterol

Abstract: We have investigated the morphology of dimyristoyl phosphatidyl choline (DMPC)-cholesterol mixed monolayer formed on the water surface by dropping method using surface tension measurement (STm), Brewster angle microscopy (BAM), and infrared external reflection spectroscopy (IERS). STm results showed negative deviation of the limiting molecular area (A 0 ) of cholesterol occurred when cholesterol was added to the DMPC monolayer. BAM images showed the expandable DMPC monolayer changed to the condensed rigid mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…It was also reported that DPPC and DMPC mixed monolayers had the properties of pure DPPC at low mole fractions of x DMPC and neat DMPC at high x DMPC , which showed their three-dimensional bulk structural properties [17]. In the above reports [13][14][15][16][17], we discussed the applications of the monolayers prepared by the DM method as a model biological membrane. Biological membrane constituents, such as phospholipids and membrane proteins, express and perform their functions using the surrounding water as a medium.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…It was also reported that DPPC and DMPC mixed monolayers had the properties of pure DPPC at low mole fractions of x DMPC and neat DMPC at high x DMPC , which showed their three-dimensional bulk structural properties [17]. In the above reports [13][14][15][16][17], we discussed the applications of the monolayers prepared by the DM method as a model biological membrane. Biological membrane constituents, such as phospholipids and membrane proteins, express and perform their functions using the surrounding water as a medium.…”
Section: Introductionmentioning
confidence: 84%
“…Each solution was spread on a purified water surface using a 50 µL syringe (Hamilton Corp., Hamilton, NY, USA) to prepare the monolayer. The details of monolayer preparation using the DM have been reported in our previous articles [13][14][15][16][17]. In brief, a drop of 1 µL volume solution was gently put on the surface of the water.…”
Section: Monolayer Formationmentioning
confidence: 99%
See 2 more Smart Citations